2016
DOI: 10.3892/etm.2016.3385
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay of pulmonary tuberculosis in patients with acute respiratory distress syndrome associated with aspiration pneumonia: Two case reports and a mini-review from Japan

Abstract: Abstract. Diagnosing active tuberculosis in elderly patients presents problems due to nonspecific symptoms and complications such as aspiration pneumonia. The current study presents two cases of pulmonary tuberculosis with bilateral pulmonary infiltrates associated with aspiration pneumonia. The two elderly patients developed acute respiratory distress syndrome as a result of aspiration pneumonia. The diagnoses of pulmonary tuberculosis were delayed in both cases, as the patients were diagnosed with active tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Elderly TB patients often present with atypical symptoms, so the diagnosis of TB can be delayed [ 6 8 ]. They also show atypical radiologic manifestations, misdiagnosed as pneumonia [ 9 , 10 ], and often need hospitalization indicated by CURB-65 (confusion, urea, respiratory rate, blood pressure, age ≥ 65) scores.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly TB patients often present with atypical symptoms, so the diagnosis of TB can be delayed [ 6 8 ]. They also show atypical radiologic manifestations, misdiagnosed as pneumonia [ 9 , 10 ], and often need hospitalization indicated by CURB-65 (confusion, urea, respiratory rate, blood pressure, age ≥ 65) scores.…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of TB had reduced to 16.7 per 100,000 among Japanese population in 2012, this figure remains 3–4 times higher than in Europe and North America [ 5 , 6 ]. One reason for the relatively high prevalence of TB in Japan is an aging population with previous TB infection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported that > 40% of older adults with TB presented with atypical features of TB in Japan [ 59 ]. The non-specific symptoms and low awareness of TB [ 60 ], especially in intermediate TB burden settings such as Japan, could lead to delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%